An Institutional Approach to Balancing International Monetary Relations : The Case for a US-China Settlement Facility - Piffaretti, Nadia F.; Rossi, Sergio (World Bank, Washington, DC, 2014)
Management of international monetary relations between China and the United States will be one of the crucial parameters for the stability or instability of the global financial system in the next decade. Although most of the literature suggests rebalancing through either adjustment of relative prices or adjustment of behavior in both countries, this paper explores an institutional approach to rebalancing. Applying the lessons from Keynes' 1944 plan for a United States-United Kingdom international clearing union, the paper explores the creation of a bilateral United States-China settlement facility as an institutional contribution to the structural rebalancing of global imbalances.